Effect of High-Dose Vitamin D on Angiogenesis Markers in High-Risk Pregnant Women - Nunki Febriastuti; Rima Irwinda; Noroyono Wibowo; Damar Prasmusinto; Yudi B. Saroyo; Yuditiya Purwosunu (Faculty of Medicine, Universitas Padjadjaran, 2026)
Preeclampsia is characterized by impaired trophoblast invasion and angiogenesis. Recent evidence suggests that vitamin D supplementation may reduce the risk of preeclampsia by optimizing angiogenesis. This study aimed to evaluate the effect of high-dose vitamin D on angiogenesis markers in the first trimester by evaluating serum maternal placental growth factor (PlGF) and uterine artery pulsality index (UtA-PI) in pregnant women with a high risk for preeclampsia. A single-blind, randomized controlled trial was conducted on 80 pregnant women from April 2021 to April 2022 at Dr. Cipto Mangunkusumo National General Hospital and Koja District Hospital. Pregnant women at 7–11 weeks of gestation were divided into low-risk and high-risk preeclampsia groups. Each group was then randomized into a control group (multi-micronutrient supplementation/MMS) and an intervention group (MMS + vitamin D at 5,000 IU/day). Maternal serum 25(OH)D levels and PlGF levels, as well as Doppler UtA-PI, were measured at baseline and after one month of intervention. All participants had vitamin D deficiency at baseline. After one month, the increase in 25(OH)D level was significantly higher in the low-risk group (12.3±6.3 ng/mL vs 10.5±5.1 ng/, p<0.001). Mean UtA-PI was significantly reduced in both low-risk (-1.1±0.3) and high-risk (-0.43±0.26) intervention groups. PlGF level increasedwas significantly in both intervention groups (low-risk 107.9±32.0 vs. high-risk 70.5±18.3, p<0.001). High-dose vitamin D supplementation (5,000 IU/day) improves angiogenesis in the first trimester, suggesting potential benefits for improving pregnancy outcomes in women at risk for preeclampsia.